In vitro bioactive properties of intact and enzymatically hydrolysed whey protein: targeting the enteroinsular axis. Issue 3 (10th February 2015) - Power-Grant, O.; Bruen, C.; Brennan, L.; Giblin, L.; Jakeman, P.; FitzGerald, R. J.
Abstract : This work identified extensively hydrolysed whey protein hydrolysates with multifunctional (insulinotropic, dipeptidyl peptidase IV inhibitory and antioxidative) bioactive properties. Abstract : Enzymatically hydrolysed milk proteins have a variety of biofunctional effects some of which may be beneficial in the management of type 2 diabetes mellitus. The purpose of this study was to evaluate the effect of commercially available intact and hydrolysed whey protein ingredients (DH 32, DH 45) on markers of the enteroinsular axis (glucagon like peptide-1 secretion, dipeptidyl peptidase IV inhibition, insulin secretion and antioxidant activity) before and after simulated gastrointestinal digestion (SGID). A whey protein hydrolysate, DH32, significantly enhanced ( P < 0.05) insulin secretion from BRIN BD11 β-cells compared to the positive control (16.7 mM glucose and 10 mM Ala). The whey protein hydrolysates inhibited dipeptidyl peptidase IV activity, yielding half maximal inhibitory concentration values (IC50 ) of 1.5 ± 0.1 and 1.1 ± 0.1 mg mL −1 for the DH 32 and DH 45, samples respectively, and were significantly more potent than the intact whey ( P < 0.05). Enzymatic hydrolysis of whey protein significantly enhanced ( P < 0.05) its antioxidant activity compared to intact whey, as measured by the oxygen radical absorbance capacity assay (ORAC). This antioxidant activity was maintained (DH 32, P > 0.05) or enhanced (DH 45, P < 0.05) following SGID. Intact whey stimulated GLP-1 secretion from enteroendocrine cells compared to vehicle control ( P < 0.05). This data confirm that whey proteins and peptides can act through multiple targets within the enteroinsular axis and as such may have glucoregulatory potential.